Determinants of Unemployment Rate in Indonesia (2011-2021 Period) - Minah, Naelul; Sekaringsih, Riswanti Budi (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2023)
This study aims to analyze the effect of economic growth, inflation, Human Development Index (HDI), Regional Minimum Wage (UMR) and investment on unemployment rates in Indonesia. The type of this study is quantitative research. Econometric analysis in this study is panel data analysis with a fixed effect model and a random effect model on the secondary data from the Indonesian Central Statistics Agency in 2011-2021 for 33 provinces. The results show that independent variables simultaneously have a significant effect on the unemployment rate in Indonesia during the period 2011-2022. Partially, the variables of Inflation, Human Development Index (HDI), Regional Minimum Wage (UMR) and investment have a significant and significant effect on the unemployment rate. At the same time, the Gross Regional Domestic Product (GRDP) variable does not affect Indonesia's unemployment rate during 2011-2022.